2014
DOI: 10.1007/978-3-319-10479-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hexavalent Chromium Resistance and Removal by Microorganisms

Abstract: Chromium has been and is extensively used worldwide in multiple industrial processes and is routinely discharged to the environment from such processes. Therefore, this heavy metal is a potential threat to the environment and to public health, primarily because it is non-biodegradable and environmentally persistent. Chromium exists in several oxidation states, the most stable of which are trivalent Cr(Ill) and hexavalent Cr(VI) species. Each species possesses its own individual chemical characteristics and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 100 publications
4
108
0
3
Order By: Relevance
“…Cr(VI) was first bound to the positively charged complexing groups on fungal surfaces, and then reduced to Cr(III) by adjacent electron-donor compounds (such as glutathione, cysteine, amino acid etc. ), or by chromate reductase excreted by the fungi [49][50][51]. In addition, it is essential to point out that a small proportion of Cr might also be absorbed by AMF as our previous study has confirmed the direct uptake and transport of Cr by ERM [20,21].…”
Section: Distribution and Speciation Of Cr In The Extraradical Mycelimentioning
confidence: 76%
See 1 more Smart Citation
“…Cr(VI) was first bound to the positively charged complexing groups on fungal surfaces, and then reduced to Cr(III) by adjacent electron-donor compounds (such as glutathione, cysteine, amino acid etc. ), or by chromate reductase excreted by the fungi [49][50][51]. In addition, it is essential to point out that a small proportion of Cr might also be absorbed by AMF as our previous study has confirmed the direct uptake and transport of Cr by ERM [20,21].…”
Section: Distribution and Speciation Of Cr In The Extraradical Mycelimentioning
confidence: 76%
“…6E), which indicates a main strategy for mycorrhizal roots to tolerate Cr(VI). Similar to extraradical mycelium mentioned above, Cr(VI) was possibly reduced by electron-donor compounds or chromate reductase in both fungal structures or plant cells [27,51,61]. Cr(III) is easily bound to phosphate, carboxyl or thiol groups, resulting in lower mobility and toxicity [27].…”
Section: Cellular Imaging and Speciation Of Cr In Resin Sections Of Mmentioning
confidence: 81%
“…48 ERM Adsorption, Accumulation, and Active Transport of Cr to Mycorrhizal Roots. Figure 2A shows that the ERM treated with Cr(VI) can accumulate more than 1000 mg kg −1 Cr.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Just as mentioned above, Cr(VI) was probably reduced to Cr(III) in the medium, in the fungi or on the fungal surface by chromate reductase or compounds that can serve as electron donors (e.g., dissolved organic carbons, cysteine, glutathione, or sulfite). 48 The Cr concentrations in the inactivated hyphae were likely associated with Cr adsorption by the fungal biomass because the inactivated hyphae exhibited a higher adsorption capacity than living hyphae. 30 Similar to previous studies on Serratia spp.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Rhizopus mampu mengubah Cr VI yang toksik dan mudah mengalami oksidasi menjadi bentuk Cr III yang lebih aman karena lebih stabil (Liu et al 2012). Cr VI berubah menjadi Cr III karena adanya kontak dengan elektron donor pada biomasa Rhizopus (Joutey et al 2015). Pada penambahan Cr dalam diet, sebaiknya dalam bentuk organik karena tidak toksik dan dapat dapat diabsorbsi dengan baik oleh tubuh (25-30%).…”
Section: Rhizopus Sp Meningkatkan Kualitas Nutrisi Pakan Ternakunclassified